SOME ASPECTS OF THE PROBLEM OF GRANITIZATION - Zharikov V.A. (My University, 1996)
The article summarizes some of the author's conclusions and results obtained during experimental and mathematical studies of granitization. The following main points are discussed: the possibility that granitization may be caused by mantle fluids; the characteristics of fusion in the presence of a fluid; the possibility that granitoid magmas may be formed in subduction zones; the absence of a particular dehydration-melting mechanism; and the association of the europium minimum with the effect of acidified solutions.